A passion for fashion: the impact of social influence, vanity and exhibitionism on consumer behaviour - Loureiro, S. M. C.; Costa, I.; Panchapakesan, P. (International Journal of Retail & Distribution Management, 2017)
Purpose The purpose of this paper is to explore the effect of social influence and individual vanity on passion for fashion of clothes and accessories and the mediating role of exhibitionist tendency. Design/methodology/approach The study was conducted in two phases. The first was exploratory (n=109), using online panel interviews, carried out among a sample of fashion enthusiasts. The quantitative phase (n=425). Shopping mall intercept field survey methodology has been utilised to collect data. Consumers who just completed their shopping and were about to leave the shopping malls were approached by trained interviewers. Findings The content analysis of phase 1 yielded four major aspects and more two aspects less cited that participants seek in posts and online information that motivate them for shopping, such as inspirational outfits, products and brands posted, self-identification with the style, value for money, friends and fashion magazines and runway shows. The findings of phase 2 reveal that the social influence is more important than individual vanity in enhancing the desire to buy and use fashion clothes and accessories. Further, the exhibitionist tendency acts as a mediator between passionate desire for fashion and self-expression word-of-mouth. Originality/value As far as authors know, this is the first attempt to explore the effect of two components of narcissism in fashion context and to analyse the social and individual influence on passionate desire to use fashion.